P.100 Early recognition of unique conventional and amplitude-integrated EEG patterns and clinical semiology of neonatal seizures caused by SCN2A and KCNQ3 mutations. (June 2022) - Pijpers, JA; Au, PY; Weeke, L; Vein, AA; Smit, L; Vilan, AI; Jacobs, E; de Vries, LS; Steggerda, SJ; Peeters, CM; Appendino, J
Abstract : Background: Early recognition of neonatal seizures secondary to pathogenic variants in potassium or sodium channel coding genes is crucial, as these seizures are often resistant to commonly used anti-seizure medications, but respond well to sodium-channel blockers. We report a unique aEEG pattern in neonatal seizures caused by SCN2A and KCNQ3 pathogenic variants, as well as adding regular EEG description. Methods: International multicentre descriptive study, reporting clinical characteristics, aEEG and conventional EEG findings of 10 newborns with seizures due to pathogenic SCN2A and KCNQ3 gene variants. Results: Seizures started in the first postnatal week. Seizure semiology typically included tonic posturing with apnea and desaturation. The aEEG showed a characteristic sequence of brief onset with a decrease, followed by a quick rise, and then postictal amplitude attenuation. This pattern correlated with bilateral attenuation in the EEG at onset, followed by rhythmic discharges ending in several seconds of post-ictal amplitude suppression. The majority of patients became seizure free upon initiation of a sodium-channel blocker. Conclusions: Neonatal seizures caused by SCN2A and KCNQ3 mutations can be recognized by a characteristic ictal aEEG pattern and clinical semiology. Awareness of this pattern facilitates the prompt initiation of precision treatment with sodium-channel blockers even before genetic test results are available.